Bibliometric Mapping of Social Media and Brand Engagement Research: Trends, Themes, and Future Direction - Anggraini, Nia; Awliya Afwa; Elondri (Jurnal Manajemen dan Keuangan, 2025)
The rapid evolution of social media has transformed how brands communicate, engage, and build relationships with consumers in the digital era. Despite extensive studies on social media marketing, limited bibliometric analysis has been conducted to systematically map research trends related to brand engagement. Therefore, this study aims to analyze the scientific development and thematic slot gacor patterns of publications discussing the role of social media in building brand engagement from 2015 to 2025. The research population comprises all Scopus-indexed articles within this topic, resulting in 1,770 publications being identified. Using the bibliometric method, data were analyzed through VOSviewer software to visualize keyword co-occurrence, relevance, and publication trends, which were subsequently classified into thematic clusters. The analysis reveals five major clusters representing the dominant themes in this field: social media marketing, customer engagement, influencer marketing, brand community, brand loyalty, and brand equity. The findings indicate that research has increasingly focused on interactive, technology-based, and emotionally driven engagement strategies. The presence of virtual influencers and AI-powered engagement tools signifies a growing emphasis on authenticity and personalization in digital brand communication. This study contributes novelty by offering a comprehensive bibliometric mapping that integrates both behavioral and technological dimensions of brand engagement. The implications highlight how social media has evolved from a communication tool into an interactive ecosystem for co-creation and emotional bonding between brands and consumers. The findings provide valuable insights for academics and practitioners to develop more adaptive, data-driven, and ethically grounded marketing strategies in the digital era.